Implementation of school disaster risk reduction in coastal schools: Basis for a plan of action - Cresencio, Marion; Yabut, Eduardo (Journal of Education and e-Learning Research, 2023)
School Disaster Risk Reduction Management (SDRRM) plays a crucial role in ensuring that learners, teachers and other school personnel are safe on the school premises. This study evaluated how well coastal schools in Cluster VII of the Division of Pampanga, Philippines had implemented a school disaster risk reduction management system. This study used the descriptive research method. Respondents to the study were seventy-four (74) public school teachers during the school year 2020-2021. In this research, the following findings were obtained: The respondents assessed safe learning facilities, school disaster management, risk reduction and resilience education and coastal school safety procedures. However, among these categories “coastal school safety procedures” got the lowest overall mean score. Additional findings showed that there is no discernible variation in the degree of SDRRM implementation across the respondent schools. This means that these schools have uniformity in implementing school disaster risk reduction management. It is recommended that schools maintain uniformity in the implementation of DRR policies.